Evaluation of wheat middlings as a supplement for cattle consuming winter range forage - Sunvold, G.D.; Cochran, R.C.; Vanzant, E.S.; Brandyberry, S.D.; Hightshoe, R.B.; DelCurto, T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Intake of dormant, bluestem-range forage was increased by feeding steers supplements based on wheat middlings or soybean meal + sorghum grain, although the degree of influence on forage intake depended on type and level of supplementation. All supplements increased (P<.10) total diet digestibility. However, fiber digestibility tended to be slightly lower for steers receiving the high level of wheat middlings and the soybean meal + sorghum grain supplement.
Keywords: Beef; Wheat middlings; Winter range forage